Recuperación funcional y bienestar psicológico en pacientes diagnosticados con esquizofrenia en entornos institucionalizados y no institucionalizados - Cornejo Carrión, Alejandra (2019)
This investigation has the goal of countering the relationship of psychological well-being in patients diagnosed with schizophrenia in institutional environments and non-institutional environments in the city of Quito. It counts with a quantitive approach, a correlational comparative scope and a non-transversal experimental design. The study will take place in an institutional environment that will be a specialized psychological hospital and in a non-institutional environment that will be a working cooperative. The sample will include a minimum of 20 participants among men and women, that have been diagnosed with schizophrenia between the ages of 18 and 45 years old that are a part of the before mentioned environments. As data collection tools we will use two psychological scales: Functional Assessment Staging (FAST) Scale to evaluate the continuous functionality of the patients and to detect the minimum changes yielded by the treatment and the Ryff Scale of Psychological Well-being, to evaluate the psychological well-being based on six main dimensions. These scales will be applied only once to each participant. Once the application is finished, and with the results we will perform a non-parametric analysis, using the Mann-Whitney U and a logistic regression analysis using as independent variables the functional recovery and psychological well-being and as a dependent variable the institutional or non-institutional environment.